Direct Hydrogen Production via Methane Decomposition - Hasan, Nur Liyana (IRC, 2016)
Hydrogen is increasingly recognized due to its potential as a sustainable and efficient fuel since the combustion of hydrogen only produced water without any greenhouse gases emission. Hydrogen is the simplest element but it is found combined with other elements, so decomposition process is required to release hydrogen. An alternative method to produce hydrogen is via methane decomposition process. However, the non-catalytic methane decomposition process is very slow at temperature below 1000˚C, thus the presence of catalyst is needed to achieve lower operating temperature. In this research work, Nickel-based metal catalysts which are monometallic nickel (Ni), bimetallic nickel promoted with molybdenum (Ni-Mo) and bimetallic nickel promoted with molybdenum added with ionic liquid (Ni-Mo-IL) supported on alumina catalysts were synthesized by wet impregnation method.